(untitled) (Mustansiria Dental Journal, 2018)
Background: In this study forces required to dislodge a maxillary complete denture were compared for different types of posterior palatal seals " Group 1 single beading design , Group 2 double beading design and group 3 with butter fly posterior palatal seal. Materials and Methods :Using a specially designed strain gauge force transducer and strain measuring device ,the force required to dislodge a maxillary complete denture measured and compared. Ten male subjects are selected with age range 55-65 yrs, the primary impression made in the usual manner and the final impression made with zinc oxide euogenol paste after the border seal made with tracing stick impression compound ,then the master cast duplicated using a heavy body silicone impression materials in order to produce a three additional casts, then the casts scraped to incorporate the posterior palatal seals and produce the three groups .a denture base constructed after postdum scraping. Results: Comparing the three groups the results shows that a significant difference found between the group 1 and 2 and group 1 and 3 with no significant difference found between group 2 and 3. Using ANOVA Table with LSD. Conclusion: No Design Provide superior priority than the other type of posterior palatal seals but a double beading and butter fly posterior palatal seal can improve the retention of a maxillary complete denture.